The Development of the Yurmash River Valley Territory at the Turn of Eras - F. F. Safuanov; A. S. Protsenko; L. V. Mambetova; P. Yu. Grabar (Историко-географический журнал)
The article presents the latest research on the settlement monuments of the Kara-Abyz culture, identified during exploration work in the Iglinsky district of the Republic of Bashkortostan. The works of 2022 confirmed the point of view of previous researchers about the development of a vast territory in depth from the main water artery of the region of the river. Belaya, on which the main monuments of the Kara-Abyz culture are concentrated. The obtained materials increased the source base of archeological monuments dated to the beginning of the 1st millennium AD, belonging to the Ubalar-Imendyashevsky cultural group, and actualized the conduct of both further reconnaissance and stationary work, with the aim of reconstructing socio-cultural processes at the final stage of the existence of the Kara-Abyz culture.